(untitled) (Bangladesh Journal of Urology, 2022)
Synthetic mid-urethral sling has become the most widely used technique for the surgical treatment of stress urinary incontinence. Despite its higher success rate significant complications have been reported including- migration, encrustation, and vesico-urethral fistula formation by a mid-urethral sling (MUS). Following the mid-urethral sling procedure, periurethral stone and urethrovaginal fistula formation are very uncommon. After an online search, we could not find any reported case of migration, encrustation and vesico-urethral fistula formation by mid-urethral sling (MUS). In this case a 55 years female presented with lower abdominal pain and incontinence, 10 years after mid-urethral sling procedure in the form of mini vaginal tape (MVT). We successfully removed the stone formed by encrustation of the displaced sling and repaired the fistula. Following the sling procedure, patients need long term follow up. Although rare, a high degree of suspicion is mandatory for diagnosis and management of complications. Bangladesh J. Urol. 2021; 24(2): 232-234